Influences of ‘Urf in Islamic Law Compilation Concerning Marriage in Indonesia - Darmawan, Darmawan (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
The scholars of ushul fiqh (uṣūliyyīn) agree that ‘urf al-ṣaḥīḥ, representing an appropriate custom, serves as the legal basis since this is congruent with what is intended in naṣ (Quran and Sunnah). Thus, determining Islamic law should take into account the customs or traditions people adhere to, including inheritance-related matters. In Indonesia, Islamic Law Compilation, the law governing inheritance based on society and religious courts, set forth several articles accommodating ‘urf in the inheritance system. This study aims to investigate which ‘urf has been adopted as a legal guideline in Islamic Law Compilation, and what implications can be caused by ‘urf in Islamic Law Compilation concerning inheritance. With an Islamic Law approach and the theory of ‘urf al-syatibi, this study concludes that there are at least four essential articles regarding the influences of ‘urf in Islamic Law Compilation, consisting of Articles 171 and 174, Article 183, and Article 190, where Article 171 point c mentions the definition of inheritor and Article 174 regulates the classification of inheritors that has an implication on the system of inheritance adopted by Islamic Law Compilation with a strong bilateral principle. Moreover, Article 183 deals with the mechanism of peace in inherited asset distribution, indicating an elaborate individual principle in Islamic Law Compilation. Article 190, however, governs the distribution of marital properties or shared properties, having an implication on the customs of the people of Indonesia who are used to equally sharing assets as adopted by Islamic Law Compilation.